PENERAPAN PERANGKAT PEMBELAJARAN IPA FISIKA BERBASIS MULTIMEDIA ICQ UNTUK MENINGKATKAN HASIL BELAJAR SISWA DI SMP/SEDERAJAT SEKOTA KENDARI SEBAGAI SEKOLAH PRAKTEK PEMBELAJARAN BAGI MAHASISWA FKIP-MIPA UHO - Sitti Kasmiati; La Harudu (Universitas Negeri Makassar, 2014)
It has conducted research-based learning tools Application Development Multimedia ICQ (Internal Control Question) to improve the quality of science teaching at the junior high school or the equivalents derby Kendari. The study was conducted with the specific aim is to improve the learning outcomes of Science-Physics and makes the SMP / equivalent derby Kendari as Learning Practice Model School, for students of Department PMIPA FKIP Unhalu to practice learning, such as (PPL, research / thesis) and other activities under the guidance of a teacher at your school and the faculty as a researcher and observer. This research method is a class action research that has been done for two cycles in class junior class VIII3 Neg. 4 and grade junior VIIIH Neg.5 Kendari in the subject matter Optical instruments. The data obtained through the instruments of the device applied qualitatively analyzed with descriptive statistics. To determine whether the application of the developed device can increase the average activity and student learning outcomes. From the analysis of the data it is concluded that: 1) Activity VIII3 grade students of SMP Negeri 4 Kendari are taught by applying multimedia learning Internal Control Question (ICQ) sufficiently increased from the first cycle to the second cycle, as shown by the average value of student activity in the first cycle of 2.8 and the second cycle increased by 0.5 to 3.3; 2) Results learn science-physics in the first cycle 62 minimum value and a maximum value 89 and the average value of 78; in the second cycle distribution obtained minimum value and a maximum value of 63 to 94 and the average value of 80. Improved learning outcomes IPA-physics can also be seen from the percentage of students who pass that in the first cycle of 84%, increasing to 87% in the second cycle. Likewise for SMP VIIIH class 5 Kendari Activities graders taught by applying multimedia learning Internal Control Question (ICQ) is quite an increase from the first cycle to the second cycle, with an average value of 2.8 in the first cycle and the second cycle the average activity of students has increased to 3.3; 2) Results learn science-physics students in the first cycle minimum value obtained 59 and maximum 92 with an average value of 73.7; Similarly, in the second cycle distribution obtained a minimum value of 63 and a maximum value of 94 with an average value of 80.0; This is also indicated by the percentage increase in the number of students who have completed, in which the first cycle of 65% rising to 90% in the second cycleTelah dilakukan penelitian Penerapan Pengembangan perangkat pembelajaran berbasis Multimedia ICQ (Internal Control Question) untuk meningkatkan kualitas pembelajaran IPA di SMP/sederajat sekota Kendari. Penelitian dilakukan dengan tujuan khusus adalah meningkatkan hasil belajar IPA-Fisika serta menjadikan SMP/sederajat sekota Kendari sebagai sekolah Model Praktikum Pembelajaran, bagi mahasiswa Jurusan PMIPA FKIP Unhalu untuk melakukan praktek pembelajaran, seperti (PPL, penelitian/skripsi) dan kegiatan lainnya dibawah bimbingan guru pada sekolah yang bersangkutan dan dosen sebagai peneliti dan observer. Metode penelitian ini adalah penelitian Tindakan Kelas yang telah dilakukan selama dua siklus di kelas Kelas VIII3 SMP Neg. 4 dan kelas VIIIH SMP Neg.5 Kendari pada materi pokok Alat-alat Optik. Data-data yang diperoleh melalui intrumen pada perangkat yang diterapkan dianalisis dengan statistik deskriptif kualitatif. Untuk mengetahui apakah penerapan perangkat yang dikembangkan dapat meningkatakan rata-rata aktivitas dan hasil belajar siswa. Dari hasil analisis data diperoleh kesimpulan bahwa: 1) Aktivitas siswa kelas VIII3 SMP Negeri 4 Kendari yang diajar dengan menerapkan pembelajaran multimedia Internal Control Question (ICQ) cukup mengalami peningkatan dari siklus I sampai siklus II, hal ini ditunjukkan dengan nilai rata-rata aktivitas siswa pada siklus I sebesar 2,8 dan pada siklus II meningkat sebesar 0,5 menjadi 3,3; 2) Hasil belajar IPA-Fisika pada siklus I nilai minimum 62 dan nilai maksimum 89 serta nilai rata-rata 78; pada siklus II diperoleh sebaran nilai minimum 63 sampai dan nilai maksimum 94 serta nilai rata-rata 80. Peningkatan hasil belajar IPA-Fisika juga dapat dilihat dari Persentase jumlah siswa yang tuntas yaitu pada siklus I sebesar 84 % meningkat menjadi 87 % pada siklus II. Demikian juga untuk kelas VIIIH SMP Negeri 5 Kendari Aktivitas siswa kelas yang diajar dengan menerapkan pembelajaran multimedia Internal Control Question (ICQ) cukup mengalami peningkatan dari siklus I sampai siklus II, dengan nilai rata-rata pada siklus I sebesar 2,8 dan pada siklus II rata-rata aktivitas siswa mengalami meningkat menjadi 3,3; 2) Hasil belajar IPA-Fisika siswa pada siklus I nilai minimum diperoleh 59 dan maksimum 92 dengan nilai rata-rata 73,7. Sama halnya pada siklus II diperoleh sebaran nilai minimum 63 dan nilai maksimum 94 dengan nilai rata-rata 80,0. Hal ini juga ditunjukkan oleh persentase peningkatan jumlah siswa yang sudah tuntas , dimana siklus I sebesar 65 % meningkat menjadi 90 % pada siklus II.Kata Kunci: perangkat pembelajaran berbasis multimedia, ICQ, hasil belajar fisika